What would you like to do?
A minus and a minus (-4+-5) is a minus. It only becomes a plus if two minus's are timesed together. eg. -4 + -5 = -9 -4 x -5 = 20 It is easier to work with if you have no …negatives on the second number. You can switch the two symbols that are next to each other without disturbing the equation. For example: -4 + -5= -4 - 5= -9 It makes it easier to trace on a number line. I hope this helps more than confuses
A positive number minus a negative number? x - -x is the same as x + x because the negative signs cancel each other out and become positive. So, when you see two ne…gative signs right after the other, just add.
2 - -9 = 2 + 9 = 11
The question isn't too clear, but I'll assume it means, "what is a negative number minus a positive number?" The answer to that is: a negative number. To explain why, imagin…e the number line. A negative number is to the left of 0. Subtraction says to go reverse the direction you would if you were adding the number. Adding a positive number would mean you're going to the right. So you just go farther to the left. Wherever you are, you're still on the left side of the 0, so the result is a negative number.
Solve one of the formulas for A, then substitute that into the other formula to solve for B, then substitute the solution for B into one of the formulas to solve for A. Here… is how: Givens: A+B=8 A-B=9 So: If A+B=8 then A=8-B Next, substitute this into the other formula... A-B=9 (8-B)-B=9 (-B) - B = 1 (-2B) = 1 B= (- 1/2) Next, substitute the solution for B into one of the formulas to solve for A.... A+B=8 A+ (-1/2) = 8 A = 8 and 1/2 So... B= (- 1/2) A = 8 and 1/2
9 - -3 = 9 + 3 = 12 12 - 8 = 4 9 - -3 - 8 = 4
Depends what you mean by "and". If they're added: never If they're subtracted: sometimes If they're multiplied or divided: always
You are taking something away a negative amount of times. Which means you are actually giving.
Answer is 43.4444
9 - - 6 + 20 = 35
yes its true because of multiplication property, for eg: (-2)(-3)=6. here -x-=+. likewise +x- or -x+ =(-). and if take another eg like (-1)^2(-1 ka whole square )= +1.
Because a minus changes the sign. If you take a plus and change it to a minus, you get a minus. If you take a minus and change it to a minus, it changes back into a plus. …Because you have only two options, minus and plus, here are all the options: + & - = -+ & + = +- & + = -- & - = + ===== Everything above the double line is a misleading, even dangerous discussion. When it's all over, both the questioner and the responder think they have it all worked out, where in reality, it's all meaningless. The main problem is: Neither of them ever explains what ' and ' means in the question, or what ' & ' means in the answer. Neither of those is a mathematical operation. The statement in the question, and the list of 4 'rules' in the answer, are correct for some mathematical operations and either indeterminate or dead wrong for others. The question says: " ... minus and minus equal plus. " -- If ' and ' means multiplication or division, then it's a true statement. -- If ' and ' means subtraction, then it may or may not be true, depending on the size of the two numbers. -- If ' and ' means addition, then it's always false. In the list of 4 items in the answer: -- If ' & ' means multiplication or division, then all 4 items are correct (but almost impossible to remember in this form). -- If ' & ' means addition, then items #1 and #3 are sometimes true and sometimes false, item #2 is always true, and item #4 is always false. -- If ' & ' means subtraction, then item #1 is always false, items #2 and #4 are sometimes true and sometimes false, and item #3 is always true.
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Pleas…e resubmit your question spelling out the symbols as "plus", "minus", "equals". There is no visible symbol between " ... equals 4" and "2b plus 1".
Taking it step by step: 2b - b - 10 = -13 b - 10 = -13 b = -13 + 10 b = - 3